Pembangunan Sosial 50 Tahun Merdeka (Social Development within 50 Years of Independence) (Jurnal Kemanusiaan, 2017)
ABSTRACTIn 2007, Malaysia celebrated the anniversary of 50 years of independence. Throughout the 50 years a lot of changes had taken place in the political system, economic and social conditions of the nation. The nation’s leaders ensured that the country will continue to develop in tandem with the changes at the global level and had the capacity to self-administer without relying on their colonialists indicating that the national administration had prioritized the welfare, prosperity and wellbeing of the people. Hence, this article attempted to uncover the social development achievements that had transpired during 50 years ago. This includes the education sector, women, employment, health and poverty. All of these sectors are among important social agendas that dominate social development, which also affects the surroundings and the quality of life of the nation’s society. The process of social development is regarded as important so that economic development activities and modernization process do not have side effects on the wellbeing of society. This article also focuses on the factor that contributed towards the achievement of social development of this nation and gives suggestions on how improvements can be made to achieve better results in future.ABSTRAKPada tahun 2007, Malaysia meraikan ulangtahun 50 tahun kemerdekaan. Sepanjang 50 tahun, banyak perubahan yang telah berlaku dalam sistem politik, ekonomi dan sosial negara. Barisan kepimpinan negara memastikan bahawa negara akan terus membangun sejajar dengan perubahan di peringkat global dan keupayaan untuk mentadbir dengan sendiri tanpa bergantung kepada pihak penjajah menunjukkan bahawa pentadbiran negara mengutamakan kebajikan, kemakmuran dan kesejahteraan rakyat. Oleh yang demikian, artikel ini cuba mengupas pencapaian pembangunan sosial yang telah dinikmati sepanjang 50 tahun yang lalu. Ini termasuklah dalam sektor pendidikan, wanita, pekerjaan, kesihatan dan kemiskinan. Kesemua sektor ini merupakan antara agenda sosial yang mendominasi pembangunan sosial yang turut mempengaruhi persekitaran dan kualiti kehidupan masyarakat negara ini. Proses pembangunan sosial dianggap penting supaya aktiviti pembangunan ekonomi dan proses modenisasi tidak memberi kesan sampingan ke atas kesejahteraan masyarakat. Artikel ini juga memberi tumpuan ke atas faktor yang menyumbang kepada pencapaian pembangunan sosial di negara ini dan memberi cadangan bagaimana penambahbaikan boleh dilakukan untuk pencapaian yang lebih baik pada masa yang akan datang.